Effectiveness of Biopore Policy Implementation in Urban Environmental Governance: A Case Study of Bandar Lampung City from the Perspective of Siyasah Tanfidziyah - Johana Nurhaliza AY; Nurnazli; Frenki (Program Studi Hukum Tata Negara, Fakultas Syariah dan Hukum Islam IAIN Bone, 2026)
This study analyzes the effectiveness of implementing Bandar Lampung City Regional Regulation No. 4 of 2022 on drainage systems, particularly the application of Biopore Infiltration Holes (BIHs), and evaluates it through the normative framework of Siyasah Tanfidziyah. The research employs a socio-legal case study approach, integrating normative legal analysis with empirical findings at the local level. The findings suggest that the implementation of BIHs is suboptimal, not solely due to technical limitations, but primarily due to a discrepancy between the scale of intervention and the complexity of urban flooding problems, as well as weak institutional capacity and insufficient social sustainability. The efficacy of BIHs is found to be contingent upon low to moderate rainfall conditions, while budgetary constraints, inadequate monitoring mechanisms, and limited community participation further constrain its sustainability. These findings demonstrate that the effectiveness of nature-based solutions, particularly BIHs, is contingent upon the integration of policy design, implementation capacity, and the institutionalization of social practices. The absence of such integration has the effect of reducing policy effectiveness and undermining the constitutional right to a healthy and sustainable environment. The study posits that the constraints on environmental policy are not exclusively technical in nature; rather, they emanate from the inability to institutionalize implementation within a cohesive governance framework. From the perspective of Siyasah Tanfidziyah, this condition is indicative of the suboptimal realization of the principles of public benefit (maslahah), justice ('adl), trust (amanah), and responsibility.